Determination of the fatigue behavior of the composite Single-Stringer structure based on the quasi-static method - Shomran, Ali Talib; Faisal, Batool Mardan; Hussein, Emad Kamil; Santos, Thiago; Fatima, Kies (Eastern-European Journal of Enterprise Technologies, 2023)
In this investigation, the Mechanical Behavior of the composite Single-Stringer structure was subjected to numerical analysis in order to better understand its properties. As the primary material for the modeling process, the carbon-epoxy IM7/8552 with quasi-isotropic Layups has been utilized. The outcomes of the numerical analysis that were carried out on the structure while it was in its static state have been put into the structural tool that was developed by the ANSYS programme. The fundamental boundary conditions have been defined on the basis of the information that was received from the testing. Static forces with a combined magnitude of 13.7 kN are being applied to the composite Single-Stringer structure. Shear stresses, direction deformation, von mises stresses, and total deformation have all been shown to have an effect on a material's mechanical behaviour, and this effect has been demonstrated. The calculations indicate that there is a maximum amount of bending that can take place as a direct result of the load that is being applied, and that amount is equal to 0.0147. The maximum amount of bending that can take place as a direct result of the load that is being applied is equal to 0.0147. As a consequence of the application of 13.7 kN of pressure, the von Mises stress, which is also frequently referred to as comparable stresses, has reached 51.9 MPa. Shear stresses have been estimated in three distinct plans, and it was discovered that the shear stress that was applied to the XY plane achieved a maximum of 15 MPa, but the shear stress that was applied to the XZ plane reached a maximum of 9.8 MPa. This was found. Both aeroplanes were put through precisely the same amount of tension at the exact same time. At this time, the shear stress on the plane YZ has reached a level of 1.5 MPa.